Complexity and Algorithms for Superposed Data Uploading Problem in Networks With Smart Devices - Li, Wenjun; Xu, Huayi; Li, Huixi; Yang, Yongjie; Sharma, Pradip Kumar; Wang, Jin; Singh, Saurabh (IEEE internet of things journal, 2020)
As a successful application of edge computing in the industrial production environment, prolonging the smart devices' (SDs') battery lifetime has become an important issue. In some special practical applications, the uploaded data from SDs to vehicle base stations (VBSs) or servers can be merged between SDs with a fixed size, which is called superposed data . In this article, we consider the superposed data uploading problem in a decentralized device-to-device communication system. The task of the problem is to minimize the total energy consumption of uploading data. We reduce it into a combinatorial optimization problem from the graph theory perspective. For VBSs or servers with infinite capacities, we propose an optimal algorithm with polynomial running time. When VBSs or servers have limited capacities, the problem is NP-hard even in very special cases. For this NP-hard problem, we give two heuristic algorithms and the corresponding numerical simulation results.